2020
DOI: 10.1038/s41598-020-60130-2
|View full text |Cite
|
Sign up to set email alerts
|

A minimal model for microbial biodiversity can reproduce experimentally observed ecological patterns

Abstract: Surveys of microbial biodiversity such as the Earth Microbiome Project (EMP) and the Human Microbiome Project (HMP) have revealed robust ecological patterns across different environments.A major goal in ecology is to leverage these patterns to identify the ecological processes shaping microbial ecosystems. One promising approach is to use minimal models that can relate mechanistic assumptions at the microbe scale to community-level patterns. Here, we demonstrate the utility of this approach by showing that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 45 publications
5
82
0
Order By: Relevance
“…We have previously shown that many of the properties of our experimental enrichment communities reflect the generic emergent behavior of consumer-resource models [14,17], and subsequent work extended this finding to complex natural communities [18]. We thus sought to ask whether our observations regarding the assembly of communities in pairs of resources are similarly reflecting a generic emergent property of consumer-resource models.…”
Section: Discussionmentioning
confidence: 75%
“…We have previously shown that many of the properties of our experimental enrichment communities reflect the generic emergent behavior of consumer-resource models [14,17], and subsequent work extended this finding to complex natural communities [18]. We thus sought to ask whether our observations regarding the assembly of communities in pairs of resources are similarly reflecting a generic emergent property of consumer-resource models.…”
Section: Discussionmentioning
confidence: 75%
“…More recently, the convex optimization approach has made it possible to perform more than 100,000 independent simulations in a reinterpretation and extension of Robert May's classic work on diversity and stability [32,33]. We have also employed the package to reproduce large-scale patterns in microbial biodiversity from the Human Microbiome Project, Earth Microbiome Project, and similar surveys [34]. Finally, the random matrix approach implemented in this package is amenable to analytic calculation in the limit of large numbers of species and resources, using cavity methods from the physics of disordered systems [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the prevalence of positive interactions and determining the conditions in which they occur could significantly improve our ability to predict and control the ecology of microbial communities (23,24). Positive interactions are predicted to enhance a community's diversity and productivity but decrease its stability (6,25,26).…”
Section: Main Textmentioning
confidence: 99%